Effect of cement-aggregate ratio and alkaline addition on the mechanical properties of compressed stabilised earth interlocking blocks - Ahmad Rashdan, Mansor (2014)
In construction field there are a lot of complex works that require time and skilled worker to handle the work. Interlocking blocks is a new method of construction where it gives a lot of advantages such as the reduction of unskilled workers, less wastage, less volume of building materials, increased environmental and construction site cleanliness and better quality control. The aims of the research are to determine the compressive strength, abrasion and water absorption of the interlocking block b'y different proportion of cement added to the aggregate. Secondly to determine the effect of alkaline solution to the compressive strength. This research was also to determine the best curing method to the interlocking blocks. Six different sets of blocks were carried out in this study. Interlocking blocks can be tested with various types of tests regarding the block's characteristic such as compression test, abrasion test and water absorption test. However the optimum mix proportion between cement, sand and laterite for compressive strength 7.0 N/mm2 load bearing wall is not determined yet. From previous research that had been done, various type of curing had been applied to the blocks but the results are uncertain. This leads to best way of curing is still unknown. The result for this research is divided into 3 category which are curing set, different ratio trial set and lastly the alkaline solution set. For the curing set, the'variables were curing under sun and curing under shade. For curing under sun, the result of compressive strength was 3.96 Mpa and under the shade was 2.12 Mpa. The next is different ratio trial set where the variables are 1:1:6 and 1:0.5:6. For ratio 1:1:6 the compressive strength was 5.63 Mpa and for 1:0.5:6 was 319 Mpa. Lastly is the alkaline solution set where the variables were 1 molarity and 2 molarity alkaline solution. For 1 molarity alkaline solution the compressive strength was 5.31 Mpa and for the 2 molarity alkaline solution was 5.40. The variables recorded that had the strongest compressive strength was the ratio of 1:1:6.